Microscopic queuing study at Batu Tiga Toll Plaza / David anak Empang - Empang, David (2006)
This study was to compare the characteristics of queuing at microscopic level of analysis at the manual and electronic toll plazas. Batu Tiga Toll Plaza was selected as the study area. The tollbooth in this plaza utilizes 3 types of toll systems; namely manual, Touch ‘n Go, and SmartTAG. The analysis at microscopic level was used in comparing the characteristics of queue in this study. For microscopic analysis, both arrival and service data were collected manually at KL bound as shown in APPENDIX F. The finding indicated that the queuing characteristics of Touch ‘n Go tollbooth was better than SmartTAG and Manual tollbooth. In addition, it was found that the drivers spent about 15 to 35 seconds to be served at the Batu Tiga Toll Plaza. The recommendation was made based on the finding and analysis done in the study.